2016
DOI: 10.3390/ijms17081255
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-18, Fetuin-A, Soluble Intercellular Adhesion Molecule-1, and Endothelin-1 in Ankylosing Spondylitis, Psoriatic Arthritis, and SAPHO Syndrome

Abstract: To examine serum interleukin 18 (IL-18), fetuin-A, soluble intercellular adhesion molecule-1 (sICAM-1), and endothelin-1 (ET-1) levels in ankylosing spondylitis (AS), psoriatic arthritis (PsA), and Synovitis Acne Pustulosis Hyperostosis Osteitis syndrome (SAPHO). We studied 81 AS, 76 PsA, and 34 SAPHO patients. We measured serum IL-18, fetuin-A, sICAM-1, ET-1, IL-6, IL-23, vascular endothelial growth factor (VEGF), and epidermal growth factor (EGF). IL-18 levels were higher in AS (p = 0.001), PsA (p = 0.0003),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 35 publications
7
41
0
1
Order By: Relevance
“…In our previous study we confirmed higher levels of IL-18 in SpA patients and AS patients [13]. In current study we additionally confirmed that serum IL-18 was higher in SpA patients with AAU and compared to healthy controls.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In our previous study we confirmed higher levels of IL-18 in SpA patients and AS patients [13]. In current study we additionally confirmed that serum IL-18 was higher in SpA patients with AAU and compared to healthy controls.…”
Section: Discussionsupporting
confidence: 88%
“…These suggested role of IL-18 in pathogenesis of SAHO [12, 13]. In our study increased serum IL-18 was associated with increased risk of PPP.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations